Chapter 8 Reusing Stepped Pools in Roman Palestinian Households - Bonnie, Rick (Taylor & Francis, 2024)
This book provides the first detailed study of the water supply of households in antiquity. Chapters explore settings from Classical Greece to the Late Roman Empire across a wide variety of environments, from dry deserts and moderate Mediterranean zones to wet and temperate climates further north. The different case studies presented in each chapter are united by three intimately interconnected aspects. The first, rainwater harvesting in cisterns, provides detailed techno-hydraulic investigations of the household water supply systems. The second aspect, households and water at the margins, stresses how domestic water supply systems were successfully adapted to unusually harsh environmental conditions. The third, other waters for houses, focuses on other types of water supply systems (rivers, water-bearers, stepped pools, wells) and their life biographies. As shown by the different chapters, a careful study of a household's water supply is a rich source of evidence for understanding everyday decisions, anxieties, and changes in life. They also build towards a greater understanding of the social inequalities that are at play in the ancient Mediterranean and beyond, providing a wealth of new research to greatly augment our understanding of water as a resource in the ancient Mediterranean. Providing a new and important perspective on a central part of everyday life in the ancient world, this book is aimed at archaeologists and historians of the ancient Mediterranean, notably the Greek and Roman worlds, especially those with an interest in ancient households and water culture.